The Ways of Restoration of Armenia’s Deficient Sovereignty within the Framework of the Changing International Legal Order - Khalatyan, Artashes (NAS RA)
This article is devoted to the examination of the legal and political foundations of the sovereignty of the Third Republic of Armenia and the revelation of the deficiencies thereof in the light of the current deep geopolitical transformation. Particularly, the former foreign policy model of Armenia is defined, and the details and consequences thereof are elucidated, i.e. Armenia pursued a client-state model of foreign policy, which implies a one-sided political stance and the vertical relationship between the patron state and client state, including a patron state’s domination in the internal policy dimensions of the client state, such as economy, internal politics, etc. It is substantiated, that as a result of the aforementioned foreign policy model Armenia lacked appropriate means of maneuver when the interests of the patron state started to contradict Armenia’s national interests. Therefore, the Armenian side lost the 44-day war and is subjected to continuous aggression from Azerbaijan.
Keywords: Legal Studies